Recent Insights into the Biosynthesis and Biological Activities of Natural Xanthones - El-Seedi, H. R.; El-Barbary, M. A.; El-Ghorab, D. M. H.; Bohlin, L.; Borg-Karlson, Anna-Karin; Goransson, U.; Verpoorte, R. (Current Medicinal Chemistry, 2010)
This review focuses on recent advances in our understanding of the complex biosynthetic pathways and diverse biological activities of naturally occurring xanthones. The biosynthesis section covers studies published from 1989 to 2008 on xanthone production in plants and fungi, while the bioactivity review presents tabulated activities of more than 250 xanthones described in studies published from 2001 to 2008, together with structural information and indications of their wide-ranging potential uses as pharmacological tools. A large number of relevant papers have been published on these subjects (128 cited here), illustrating the diversity of the xanthones and their possible uses.
Keywords: Biological activity